Investigating consumer intentions on online power bank rental self-service retailing - Gienzka Azzahra Wibowo Putri; Chairy Chairy (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The growth of online rental self-service business models used to borrow various kinds of goods has been growing in Indonesia. The online rental self-service utilizes sophisticated technology and logistics to provide the right products in the form of a digital platform. This digital platform allows online rental self-service to be more efficient, influencing consumer behavior intentions. Based on the theory of reasoned actions, technology acceptance model, expectancy-value and perceived risk, this study aims to investigate behavioral beliefs that can cause them to form favourable intentions in the online rental self-service power banks. In this research, 149 samples of survey results were obtained from users of ReCharge, the power bank online rental self-service in Indonesia. Partial least squares structural equation modelling (PLS-SEM) was used for this study. Results emphasize that relative advantage, compatibility, psychological ownership, and ecological importance have a significant relationship with the intention to rent a power bank online and can be mediated by user attitude. Subjective norms and perceived risk also have a significant relationship in renting a power bank online. However, perceived ease of use and perceived usefulness do not have a significant relationship with the intention to rent a power bank online. This study offers appropriate business strategies that can be designed to increase consumer engagement in adapting the digital growth and expanding the market.